Research on PCK Theory Based on Core Literacy -- A Case Study of High School Physics Teaching - Zhang, Yue (Journal of Education and Educational Technologies, 2023)
The core quality of physics in senior high school aims to train students to understand nature from the perspective of physics, understand nature, learn to explore, experience scientific research methods and develop scientific thinking habits. Teachers should have certain means in the leading process. Therefore, under the premise of taking the core literacy of physics as the guidance, this paper, through the content of the basic core literacy of physics, once again studies the teacher's PCK theory of Schulmantift, analyzes the content of the PCK theory and its specific guiding role in teaching, summarizes the basic methods to achieve the core literacy of physics, and summarizes the construction process of the teacher's PCK theory.